Numerical Simulation of Rock Failure Process with a 3D Grain-Based Rock Model. (31st July 2020) - Zhang, Zengwei; Chen, Fan; Zhang, Chao; Wang, Chao; Wang, Tuo; Zhang, Fengshou; Zhao, Huiling
Abstract : A grain-based rock model was developed and applied to study mechanical characteristics and failure micromechanics in thick-walled cylinder and wellbore stability tests. The rock is represented as an assembly of tetrahedral blocks with bonded contacts. Material heterogeneity is modeled by varying the tensile strength at the block contacts. This grain-based rock model differs from previous disk/sphere particle-based rock models in its ability to represent a zero (or very low) initial porosity condition, as well as highly interlocked irregular block shapes that provide resistance to movement even after contact breakage. As a result, this model can reach higher uniaxial compressive strength to tensile strength ratios and larger friction coefficients than the disk/sphere particle-based rock model. The model captured the rock fragmentation process near the wellbore due to buckling and spalling. Thin fragments of rock similar to onion skins were produced, as observed in laboratory breakout experiments. The results suggest that this approach may be well suited to study the rock disaggregation process and other geomechanical problems in the rock excavation.